Respuesta :
The answer is: " 3 " .
__________________________________________________
Explanation:
________________________________________________________
(3/4) ÷ (1/4) = (3/4) * (4/1) = ?
The "4's" cancel out to "1's" ; → {since: "4 ÷ 4 = 1 " } ;
And we can rewrite the expression as:
" (3/1) * (1/1) " ;
→ " (3/1) * (1/1) = 3 * 1 = " 3 " .
__________________________________________________
The answer is: " 3 " .
__________________________________________________
__________________________________________________
Explanation:
________________________________________________________
(3/4) ÷ (1/4) = (3/4) * (4/1) = ?
The "4's" cancel out to "1's" ; → {since: "4 ÷ 4 = 1 " } ;
And we can rewrite the expression as:
" (3/1) * (1/1) " ;
→ " (3/1) * (1/1) = 3 * 1 = " 3 " .
__________________________________________________
The answer is: " 3 " .
__________________________________________________